2014
DOI: 10.4238/2014.may.13.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of EST-SSR markers related to salt tolerance and their application in genetic diversity and evolution analysis in Gossypium

Abstract: ABSTRACT. Salt stress is becoming one of the major problems in global agriculture with the onset of global warming, an increasing scarcity of fresh water, and improper land irrigation and fertilization practices, which leads to reduction of crop output and even causes crop death. To speed up the exploitation of saline land, it is a good choice to grow plants with a high level of salt tolerance and economic benefits. As the leading fiber crop grown commercially worldwide, cotton is placed in the moderately salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
(34 reference statements)
0
14
1
Order By: Relevance
“…Ten of the 46 markers used in this study showed a medium level of polymorphism; 36 markers were highly polymorphic, whereas no markers showed a low level of polymorphism, thus indicating that these EST-SSR markers can provide abundant genetic information and that there was wide genetic diversity between the cotton accessions adopted in this study. The average PIC value of these disease-resistant EST-SSR markers (0.6458) were even higher than that of salt-tolerant EST-SSR markers reported in our previous study (0.4810) (Wang et al, 2014a).…”
Section: Development Amplification and Characteristics Of Disease-rcontrasting
confidence: 67%
See 1 more Smart Citation
“…Ten of the 46 markers used in this study showed a medium level of polymorphism; 36 markers were highly polymorphic, whereas no markers showed a low level of polymorphism, thus indicating that these EST-SSR markers can provide abundant genetic information and that there was wide genetic diversity between the cotton accessions adopted in this study. The average PIC value of these disease-resistant EST-SSR markers (0.6458) were even higher than that of salt-tolerant EST-SSR markers reported in our previous study (0.4810) (Wang et al, 2014a).…”
Section: Development Amplification and Characteristics Of Disease-rcontrasting
confidence: 67%
“…Previous studies indicated that the effective amplification rate of EST-SSRs should be 60 to 90% (Saha et al, 2004), and that some primers may not be amplified once the primer covers an mRNA editing site or the amplification product contains large introns. In our previous study, the effective amplification rate was 80.3% (Wang et al, 2014a). In the current study, clear bands were amplified in 84 of the 106 NTU primer pairs, and the effective amplification rate was 79.3%, which is a high value compared to values reported in previous studies.…”
Section: Development Amplification and Characteristics Of Disease-rmentioning
confidence: 86%
“…CCRI12 and G. hirsutum L. Xinyan96-48, with 274 SSR markers, and subsequently identified 10 primer pairs that could be used to detect salt-tolerance in cotton. Wang et al (2014) developed a total of 132 pairs of non-redundant expressed sequence tag-simple sequence repeat (EST-SSR) primers related to salt-tolerance according to salt-resistant cotton ESTs and performed genetic diversity and evolution analyses on cotton. To some extent, these studies have accelerated the application of molecular markers to the breeding of salt-tolerance in cotton.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs from expressed sequence tags (EST-SSRs) are markers that may be used between species belonging to different genera. The EST provides a source of polymerase chain reaction (PCR)-based markers for SSR direction (Wang et al, 2014). In the present study, we evaluated the transferability of EST-SSR markers described for Catharanthus roseus to H. speciosa.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers (SSRs) have been widely used to answer questions related to population genetics (Gonzalés-Pérez et al, 2009;Madesis et al, 2014;Wang et al, 2014). However, microsatellites are expensive to use and it is time-consuming to develop specific primers for each locus of the native species (Zucchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%